Integration of Technology and Character Education in the Teaching Campus 6 Program at GMIM Tonsea Lama Elementary School: Transforming Learning in the Digital Era - Romi Mesra; Preseisilya Selly Palimbong (PT. NALURI EDUKASI PRESS, 2025)
This study aims to analyze the implementation of technology integration and character education through the Teaching Campus Program at GMIM Tonsea Lama Elementary School and explore its impact on learning transformation in the digital era. The research method uses a qualitative approach with a case study design, with data collection techniques through methodological triangulation including participant observation, documentation, and in-depth interviews. Data analysis was conducted using the Miles and Huberman thematic analysis model with the stages of data reduction, data presentation, and conclusion drawing. The results of the study show significant success in improving students' literacy skills from 52% to 77% and numeracy from 38% to 67% through innovative programs such as